Sensory analysis of commercial anchovy fish and anchovy from non-commercial standard tilapia (Research, Society and Development, 2022)
Fish industry has been looking for alternatives and forms of processing. Among the most cultivated species in Brazil, Nilo tilapia is marketed mainly in frozen fillets. The objective of this work was to analyze the acceptance of tilapia, as a salted product, similar to anchovies that are sold in supermarkets and have high values. In this way, homemade salting of tilapia was prepared, using the clean trunk of animals between 100 and 300 grams in a similar way to the preparation of anchovies. This homemade product was submitted to acceptance test and sensory analysis along with the commercial anchovy, found for sale in supermarkets. The samples were submitted to 41 untrained evaluators who assigned scores from 1 to 9, on a hedonic scale, according to the Dutcosky methodology. Attribute data were subjected to analysis of variance using the paired t test. To graphically analyze the effect of the multivariate dispersion of treatments, a Permanova was also performed. Appearance, flavor, aroma and color were considered statistically equal at the 5% level by the Tukey test. The percentage of evaluators who gave equivalent scores to liked the products was greater than 50% in all attributes. About 70% of the evaluators gave notes indicating that they liked the taste. Therefore, the use of tilapia similarly to anchovy can be a viable alternative to aggregate value to fish.